ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ULANG PELANGGAN (Studi pada pelanggan mobile & electronics di situs online Bukalapak) - Priambudi, Dicka; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2019)
The development of the digital world that has expanded in various ways is no stranger to today's life, as well as in meeting everyday needs. The development of e-commerce business is a real proof of the seriousness of various parties in facing the progress of the era. Trade competition is getting tougher, which requires the right marketing strategy, in order to attract the purchasing power of the people. This study aims to analyze how the influence of customer satisfaction repurchase mobile & electronic customers on the Bukalapak site. The population in this study are users or Bukalapak online shop customers who are still active and have bought mobile & electronics products on the site. The results showed that web quality, and trust have a positive effect on customer satisfaction, and customer satisfaction, web quality, and trust have a positive effect on repurchase, but web quality has a major effect on influencing repurchases.